Minimal Stimulation IVF vs Conventional IVF: A Randomized Controlled Trial. Issue 4 (April 2016) - Zhang, John J.; Merhi, Zaher; Yang, Mingxue; Bodri, Daniel; Chavez-Badiola, Alejandro; Repping, Sjoerd; van Wely, Madelon
Abstract : Obstet Gynecol Surv 2016;71(4):228–229 Women receiving conventional in vitro fertilization (IVF) treatment are at risk of ovarian hyperstimulation syndrome (OHSS) and multiple pregnancies.